The 'Mangetar Trap'? Work, family and Pakistani migrant husbands. Issue 2 (3rd April 2019) - Charsley, Katharine; Ersanilli, Evelyn
ABSTRACT: Contemporary immigration from Pakistan to the UK often takes the form of marriage migration, as substantial numbers of British men and women of Pakistani ethnicity marry partners from Pakistan. Drawing on quantitative and qualitative evidence, this paper explores experiences of Pakistani men migrating to the UK through marriage, revealing a complex of social and economic pressures in the early months and years post-migration, here referred to as the 'Mangetar Trap'. Migration can have contradictory implications for masculinity – presenting both opportunities and challenges for gendered aspirations. The existing research literature reveals instances of migrant men using the former to compensate for the latter. For some recently arrived Pakistani migrant husbands in Britain, however, particular combinations of socio-economic position, time poverty, social marginalisation and family relationships can constrain their available options. In the longer term, such men may find routes to improving their situations, but exploration of these early constraints is valuable in cautioning against an over-emphasis on agency in research on migrant masculinity.